Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
y-2x=-6 and 5x-y=9
step 1: isolate y in the first equation
y = 2x - 6
step 2: substitute the y value on the 2th equation:
5x-(2x-6)=9
step 3: solve the present equation:
5x - 2x + 6 = 9
3x = 9-6
3x = 3
x = 1
step 4: get the y value by replacing the value of x in y = 2x - 6:
y = 2*1 - 6
y = 2 - 6
y = -4
S={1, -4}
step 1: isolate y in the first equation
y = 2x - 6
step 2: substitute the y value on the 2th equation:
5x-(2x-6)=9
step 3: solve the present equation:
5x - 2x + 6 = 9
3x = 9-6
3x = 3
x = 1
step 4: get the y value by replacing the value of x in y = 2x - 6:
y = 2*1 - 6
y = 2 - 6
y = -4
S={1, -4}
[tex] \left \{ {\big{y-2x=-6} \atop\big {5x-y=9\ \ }} \right. \\\\ \left \{ {\big{y=2x-6\ \ \ \ \ \ \ \ \ \ } \atop\big {5x-(2x-6)=9\ \ }} \right. \\\\ \left \{ {\big{y=2x-6\ \ \ \ \ \ \ \ \ \ } \atop\big {5x-2x+6=9\ \ }} \right. \\\\ \left \{ {\big{y=2x-6\ \ } \atop\big {3x=3\ /:3 }} \right. \\\\ \left \{ {\big{y=2x-6 } \atop\big {x=1\ \ \ \ \ \ }} \right. \\\\ \left \{ {\big{y=-4 } \atop\big {x=1\ }} \right. \\\\[/tex]
[tex]Ans.\ \left \{ {\big{x=1} \atop\big {y=-4}} \right. \ \ \ \Rightarrow\ \ \ point:\ \ (1;-4)[/tex]
[tex]Ans.\ \left \{ {\big{x=1} \atop\big {y=-4}} \right. \ \ \ \Rightarrow\ \ \ point:\ \ (1;-4)[/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.